Textual and linguistic characteristics in ELT research article abstracts: Insights from Indonesian novice writers - Malik, Zulfikri; Setiawan, Slamet (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
In academic writing, particularly in research article abstracts, rhetorical moves and linguistic features are pivotal for effectively communicating findings to a broad audience. This study explores the rhetorical moves employed by Indonesian novice writers in their research article abstracts and their linguistic realization. Using a descriptive qualitative design, we analyzed 25 English Language Teaching (ELT) abstracts written by Indonesian novice writers, employing a checklist instrument for data collection. The results indicate that purpose and product moves are obligatory, method and conclusion moves are conventional, and introduction moves are optional. Rhetorical patterns predominantly follow a linear structure, with embedded and less frequent moves occurring less often. Linguistically, active voice prevails across all moves, surpassing passive voice usage. Present tense is the most common, followed by past, perfect, and future tenses. Key interactional metadiscourse devices, including hedges, boosters, and attitude markers, are evident, while engagement markers and self-mentions are notably absent. This study underscores variations in rhetorical structures and linguistic features among Indonesian novice writers, offering insights to enhance their academic writing practices.